A High Triglyceride-Glucose Index Value Is Associated With an Increased Risk of Carotid Plaque Burden in Subjects With Prediabetes and New-Onset Type 2 Diabetes: A Real-World Study - Jiang, Zhen-zhen; Zhu, Jian-bo; Shen, Hua-liang; Zhao, Shan-shan; Tang, Yun-yi; Tang, Shao-qi; Liu, Xia-tian; Jiang, Tian-an (Frontiers in Cardiovascular Medicine, 2022)
Background: The triglyceride-glucose (TyG) index has been proposed as a convincing indicator of insulin resistance and has been found to be associated with atherosclerosis among diabetic patients. However, the relationship between the TyG index and arteriosclerosis in subjects with prediabetes and new-onset type 2 diabetes (T2D) remains uncertain. The purpose of this study was to assess the degree of carotid plaque burden in patients with prediabetes and new-onset T2D and to investigate the association between the TyG index and the degree of carotid plaque burden in this population. Methods: This was a cross-sectional observational study that included 716 subjects aged 40-70 years old with prediabetes or new-onset T2D. Demographic, anthropometric, and laboratory measurements were collected. Participants underwent carotid arteriosclerosis evaluation by ultrasonography, and the the degree of atherosclerosis was evaluated according to the carotid plaque burden. The TyG index was calculated. Results: The population was stratified into high or low TyG index groups according to the median TyG index value. Higher values were associated with a higher BMI and waist circumference as well as higher total cholesterol, triglyceride, low-density lipoprotein cholesterol, plasma glucose, glycated haemoglobin, fasting C-peptide, and C-reactive protein levels (P < 0.001). The high TyG index group had a higher atherosclerotic plaque burden than the low TyG index group (P < 0.001). Multiclassification logistic regression analysis showed that the TyG index was positively associated with a high plaque burden [odds ratio (OR): 16.706, 95% confidence interval (CI): 3.988-69.978, P =0.000], while no association was found between the TyG index and a low/moderate plaque burden. This association remained consistent in the subgroup analysis. In multiple linear regression analysis, sex, age, and the TyG index were found to be independently associated with carotid plaque burden. For each unit increase in the TyG index, the risk of a high carotid plaque burden increased 1.595-fold. Conclusion: A high TyG index was positively associated with a high carotid plaque burden in subjects with prediabetes and new-onset T2D. Clinicians should pay close attention to the TyG index to help these patients receive the greatest benefit from early intervention.